2013
DOI: 10.1523/jneurosci.4806-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Ingestion Induces Rapid AMPA Receptor Trafficking

Abstract: The mechanisms by which natural rewards such as sugar affect synaptic transmission and behavior are largely unexplored. Here, we investigate regulation of nucleus accumbens synapses by sucrose intake. Previous studies have shown that AMPA receptor trafficking is a major mechanism for regulating synaptic strength, and that in vitro, trafficking of AMPA receptors containing the GluA1 subunit takes place by a two-step mechanism involving extrasynaptic and then synaptic receptor transport. We report that in rat, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 55 publications
(90 reference statements)
6
40
0
Order By: Relevance
“…Despite the accumulating evidence for a role of GluA2-lacking AMPA receptors in the expression of LTP in several brain regions [18,[25][26][27][28], there is controversy as to the role GluA2-lacking AMPA receptors play in the expression of hippocampal LTP. Two studies failed to find evidence for such a role forGluA2-lacking AMPA receptors [29,30]; however, two other studies do provide evidence for incorporation of GluA2-lacking AMPA receptors in LTP [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the accumulating evidence for a role of GluA2-lacking AMPA receptors in the expression of LTP in several brain regions [18,[25][26][27][28], there is controversy as to the role GluA2-lacking AMPA receptors play in the expression of hippocampal LTP. Two studies failed to find evidence for such a role forGluA2-lacking AMPA receptors [29,30]; however, two other studies do provide evidence for incorporation of GluA2-lacking AMPA receptors in LTP [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Since these early studies on the involvement of GluA2-lacking, calcium-permeable AMPA receptors in cerebellar and hippocampal synaptic plasticity, a number of studies have shown that similar mechanisms may underlie plasticity in other brain areas, including primary sensory cortex, ventral tegmental area (VTA), amygdala and hypothalamus [18,[25][26][27][28]. Despite this, considerable controversy remains for hippocampal CA1 LTP on the role of GluA2-lacking AMPA receptors.…”
Section: Introductionmentioning
confidence: 99%
“…These unique biophysical properties enable CPARs to play an important role at the synapse, including the induction of long-term potentiation (LTP) or long-term depression (LTD) [16, 27, 35]. By regulating synaptic strength, CPARs modulate a diverse set of behaviors [14, 15, 24, 34, 55, 56]. Our data raises the possibility of CPAR formation in both the core and shell subregions in pain states.…”
Section: Discussionmentioning
confidence: 84%
“…A number of studies have described GluA1 upregulation in the NAc after repeated or prolonged consumption of natural rewards or cocaine [45, 55]. In these studies, homeostatic plasticity has been posited as a possible mechanism for the increase in GluA1 subunits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation